2012
DOI: 10.1093/eurheartj/ehs425
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of remote follow-up of implantable cardioverter defibrillators: safety and efficacy report of the ECOST trial

Abstract: AimsThe ECOST trial examined prospectively the long-term safety and effectiveness of home monitoring (HM) of implantable cardioverter defibrillators (ICD).Methods and resultsThe trial's primary objective was to randomly compare the proportions of patients experiencing ≥1 major adverse event (MAE), including deaths from all causes, and cardiovascular, procedure-related, and device-related MAE associated with HM (active group) vs. ambulatory follow-ups (control group) in a sample of 433 patients. The 221 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(262 citation statements)
references
References 20 publications
8
226
0
12
Order By: Relevance
“…Remote monitoring permits an earlier reaction to events requiring physician intervention in comparison to regular in-office device checks, with 98.6% of transmissions being reviewed within two working days in our cohort. (3,4,6,(14)(15)(16)(17)(18)(19)(20)(21) Early detection allows prompt management of arrhythmias, early management of device malfunction and device reprogramming to reduce inappropriate defibrillator shocks. (18,22,23) Compliance to remote monitoring was good, with an overall missed transmission rate of 11.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring permits an earlier reaction to events requiring physician intervention in comparison to regular in-office device checks, with 98.6% of transmissions being reviewed within two working days in our cohort. (3,4,6,(14)(15)(16)(17)(18)(19)(20)(21) Early detection allows prompt management of arrhythmias, early management of device malfunction and device reprogramming to reduce inappropriate defibrillator shocks. (18,22,23) Compliance to remote monitoring was good, with an overall missed transmission rate of 11.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a cause-effect relationship that still needs to be definitively demonstrated, there is recent evidence that RM might be associated with a reduction of inappropriate ICD shocks [20]; emergency department or urgent in-office visits for heart failure, arrhythmias, or ICD-related events [21]; and even mortality [9]. Such potential clinical benefit might be explained by early detection of critical events: in the CON-NECT trial [11], the median time from clinical event to clinical decision per patient was reduced from 22 days in the control group to 4.6 days in RM group.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Moreover, these adverse events detected by RM are often silent [5] and, in the case of AF, occurred in about 30 % of the patients as new onset AF [23]. Such early diagnosis may reduce the rate of hospitalization and/or length of in-hospital stay [11], decrease the incidence of strokes [26,27], and reduce the number of inappropriate shocks causing early depletion of ICD therapy [20,22]. Such clinical benefit may result in an additional and even more important reduction of overall healthcare resource consumption, making RM economically attractive.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Considering that the number of patients with implantable devices is increasing, there are attempts being made to include these patients in remote monitoring systems (RM). The most debatable issue concerning RM is safety issue, especially in the case of ICDs and CRT-D. Guédon--Moreau et al [23] in the ECOST trial confirmed the safety and effectiveness of RM of patients with ICDs. Moreover, patients controlled by RM had significantly lower incidence of NI and INAI and up to 72% less hospitalizations.…”
Section: Resultsmentioning
confidence: 95%